Investigation of the Allelopathic Effect of Matricaria chamomilla L. Parts’ Aqueous Extracts on Germination and Seedling Growth of Two Moroccan Varieties of Durum Wheat - Amine Elbouzidi; Noureddine Bencheikh; Sara Seddoqi; Mohamed Bouhrim; Youssef Bouramdane; Mohamed Addi (International Journal of Agronomy)
The phenomenon of allelopathy has been known for more than 2000 years. This phenomenon consists of the chemical interference of plant species (or other organisms), by enhancing, or inhibiting, the germination, seedling growth, or development of other plant species (or other organisms). This paper aimed to investigate the allelopathic potential of the aqueous extract of different parts of Matricaria chamomilla L. on germination parameters (radicle, coleoptile length, and dry weight) of two Moroccan varieties of durum wheat. Chamomile extracts from leaves, roots, or flowers at concentrations of 50 and 100 g·L−1 were prepared and applied to wheat durum seeds. The control group was given distilled water. In both studied varieties of durum wheat, only flowers’ aqueous extracts showed a significant positive allelopathic effect by increasing the studied parameters, while leaves and roots from chamomile showed an inhibiting potential on germination and seedling growth in varieties riyad and kanakis.